Protein or amino acid supplementation on the physical performance of athletes: A meta-analysis - Portuguez Molina, Priscilla (2024)
It is known that protein supplementation in the general population has effects on strength, muscle mass and improvements in sports performance. Since athletes vary their characteristics from the general population; protein supplementation should be studied in more detail on them. There are few studies on endurance athletes in the area and this specific group could benefit from increasing their protein intake. PURPOSE: To determine the effect size of protein or amino acid supplementation on sports performance of endurance athletes (triathlon, swimming, cycling and running); through the meta-analytic technique. METHODS: PRISMA guidelines were followed. A systematic literature search was conducted in the following databases: PubMEd, EBSCO Host (Academic Search Ultimate, Fuente Académica Plus, MEDLINE with full text, SPORTDiscus with full text) and Web of Science. Experimental and quasi-experimental studies that investigated the effects of protein or amino acids chronic supplementation on the physical performance of athletes of four different sports were included. Within-group comparisons were made to calculate effect sizes (ES), using the random effect model. RESULTS: After the initial search, 376 full-text articles were reviewed and a total of 27 studies that met all the criteria were included, for a total of 118 effect sizes: 60 for the experimental group and 58 for the control. When performing the global ES analysis, a value of 0.166 was obtained (p=0.007; CI = 0.045 to 0.287; Q = 43.586; I2 =0) for the experimental group and 0.057 (p=0.364; CI = -0.066 to 0.180; Q = 15.516; I2 =0) for the control group. Moderator variables were analyzed. Variables like sex, sport level, type of performance, ingestion time for the supplementation, among others; revealed a significant ES in some subgroups. Funnel Plot graph and the Egger test did not reveal presence of bias. CONCLUSION: When supplementing with protein or amino acids, certain variables that can change their effect on physical performance must be evaluated. Nutritional evaluation during the supplementation period should be considered as an essential part of the intervention as it could be a factor that limits the benefits of supplementation with protein or amino acids.